PERWAKAFAN TANAH PEMAKAMANAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Samiah Samiah; Zarul Arifin; Hasiah Hasiah (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This research aims to find out Islamic law regarding the endowment of burial grounds. This type of research is a juridical-empirical approach, used to analyze various statutory regulations related to waqf land while the empirical approach is used to analyze law as patterned community behavior in people's lives. The data analysis method uses an inductive method starting from general to specific. The research results show that changing the function of burial waqf land into private property is not permitted in Islamic law, because the land has been donated so it cannot be taken back or repurposed. In the legislation regarding waqf in Indonesia, objects that have been donated cannot be transferred. For the act of transferring waqf objects, a criminal sanction of imprisonment for a maximum of 3 (three) months and a fine of up to idr. 10,000 (ten thousand rupiah).